Population genetic data of 22 autosomal STR loci for the Scheduled Caste population of Rajasthan India - Anand Kumar; Rajesh Kumar; R. K. Kumawat; Pankaj Shrivastava; Rajesh Yadav; Gyaneshwer Chaubey (Taylor & Francis Group, 2021)
Aim To study the genetic structure of the Scheduled Caste population of Rajasthan and its relationship with Indian and global populations using expanded 20 CODIS STR loci (autosomal) markers. Subjects and methods Blood samples of 226 healthy, unrelated adult individuals of the Scheduled Caste population of the Indian state of Rajasthan were taken from the routine casework of authors after obtaining written informed consent. Autosomal STR markers included in PowerPlex® Fusion 5 C and GlobalFiler™ PCR amplification kits were used to explore the genetic diversity of the studied population. Amplicons were separated using Genetic Analyser 3500XL as per the recommended protocol. Results Observed heterozygosity for the studied population ranged from 0.681(CSF1PO) to 0.881 (D1S1656).Combined Discrimination Power and Combined Exclusion Power were observed as 1 and 0.9999999852, respectively. The highest Discrimination Power was observed for the locus D1S1656. In the population comparison test, Nei's Da distance-based Neighbor-Joining (NJ) dendrogram revealed two significant clusters of geographically close Indian and East Asian populations along with a few small groups of outlier populations. Conclusion The matching probability for 20 STR markers was observed as 7.02 × 10−24 and paternity index as 5.55 × 107. These values play a key role in forensic applications.The studied population showed a higher genetic affinity with geographically closer populations than the distant ones. This caste-based population data is expected to play an important role in forensic DNA applications and genetic studies.